Digital monitoring of posts related to amber necklaces to prevent teething symptoms on Facebook - Jorge, Olívia Santana (2023)
Posts recommending and marketing amber necklaces for the prevention of teething symptoms can be easily found on social media. Considering that these posts contribute to the reinforcement of false health beliefs and that the use of amber necklaces poses risks to children, this study aimed to characterize Facebook posts containing false information about the effectiveness of amber necklaces for preventing deciduous teething symptoms and identify factors present in the messages associated with greater user engagement. Using the CrowdTangle tool, samples of 500 posts in English (article 1) and 500 posts in Portuguese (article 2) were obtained, all published between August 2016 and August 2021. The collected data also included interaction metrics and publication dates of the posts. The posts were qualitatively analyzed by two independent investigators (ICC0.8) in terms of profile (regular users or business), sentiment (positive or neutral/negative), and motivation (financial or non-financial). They were also quantitatively analyzed in terms of time since publication, total user interactions, and overperforming scores. For the analysis of English posts, latent Dirichlet allocation (LDA) topic modeling was also used to identify relevant terms and topics, and a topic distance map was created to calculate the similarity between them. The data were statistically analyzed using descriptive analysis, Mann-Whitney U test, Cramer\'s V test, and multiple logistic regression models, considering the time since the initial post and interaction metrics. For the English analysis (article 1), the majority of posts were from business profiles (73.2%), had a positive sentiment (93%), motivations related to social (100%), psychological (98.4%), and financial gains (95.6%), and were presented in photo format (86.4%). The posts were categorized into the topics of \"giveaway,\" \"healing features,\" and \"sales.\" Increased total interaction was associated with longer time since publication (OR=1.789; p=0.002), and higher overperforming scores were associated with posts containing links (OR=2.403; p=0.002). For the Portuguese analysis (article 2), the majority of posts were from business profiles (82.4%), had a positive sentiment (92.2%), had motivations related to social (100%), psychological (100%), and financial gains (91.0%), and were presented in photo format (94.6%). Higher total interaction was associated with regular user profiles (OR=3.297; p<0.001), longer time since publication (OR=2.648; p<0.001), and neutral/negative sentiment (OR=2.758; p=0.022), while overperforming scores were directly associated only with longer publication time (OR=1.646; p=0.006). Facebook posts about the effectiveness of amber necklaces for preventing teething symptoms, both in English and Portuguese, are primarily motivated by financial interests and use psychological and social mechanisms to achieve higher engagement with their target audience.